Developing an expressive writing program model for strengthening students’ mental resilience against bullying - Muraina Kamilu Olanrewaju; Febi Robianti; Obinna Augustine Anum; Atawodi Ibrahim; Kennedy Shuaibu (International Journal of Public Health Science (IJPHS), 2026)
Bullying remains a persistent issue in schools and continues to undermine students’ emotional and psychological well-being. This paper introduces a novel conceptual model of an expressive writing program specifically designed for Indonesian schools, addressing the current gap in structured resilience-building interventions. Using a qualitative design based on secondary data from books and journal articles, this study outlines how expressive writing can be systematically integrated into school settings to strengthen students’ mental resilience. The proposed model-illustrated in the program diagram-combines guided writing sessions, emotional literacy activities, and teacher-facilitated support mechanisms. The program also emphasizes teacher preparedness, safe classroom environments, and collaborative involvement from parents and counselors. Additionally, secure digital platforms are recommended to enhance accessibility and ensure confidentiality. This model is intended to guide schools in implementing proactive emotional support systems and to provide a foundation for future empirical evaluation of its effectiveness in reducing bullying and improving students' emotional well-being.